A Designer’s Approach for Estimation of Nuclear-Air-Blast-Induced Ground Motion - Shashank Pathak; G. V. Ramana (Advances in Civil Engineering)
A reliable estimate of free-field ground displacement induced by nuclear-air-blast is required for design of underground strategic structures. A generalized pseudostatic formulation is proposed to estimate nuclear-air-blast-induced ground displacement that takes into account nonlinear stress-strain behaviour of geomaterials, stress-dependent wave propagation velocity, and stress wave attenuation. This proposed formulation is utilized to develop a closed-form solution for linearly decaying blast load applied on a layered ground medium with bilinear hysteretic behaviour. Parametric studies of closed-form solution indicated that selection of appropriate constrained modulus consistent with the overpressure is necessary for an accurate estimation of peak ground displacement. Stress wave attenuation affects the computed displacement under low overpressure, and stress-dependent wave velocity affects mainly the occurrence time of peak displacement and not its magnitude. Further, peak displacements are estimated using the proposed model as well as the UFC manual and compared against the field data of atmospheric nuclear test carried out at Nevada test site. It is found that the proposed model is in good agreement with field data, whereas the UFC manual significantly underestimates the peak ground displacements under higher overpressures.